X-efficiency and Loan Loss Provision of Hong Kong Banking - Han, Runyue (2017)
Abstract This thesis shows the changes of Hong Kong banking system these years. And it estimates the X-efficiency (cost efficiency) of Hong Kong banks from 2011 to 2016, and also analysis the possible determinants of X-efficiency. The loan loss provision decision of Hong Kong banks is also analysed in this thesis. Based on the Battese and Coelli (1995) model with stochastic frontier approach, this thesis found that Hong Kong banking system has high cost efficiency. Generalised-method-of-moment technique is used to establish a dynamic model for loan loss provision study. The results show that Hong Kong banking system does not follow three hypothesis (procyclicality, capital management and income-smoothing). The shining point of this thesis is that the cost efficiency and lagged value of cost efficiency involved in loan loss provision model for Hong Kong banking system from 2011 to 2016.